Eco Bamboo Creation: Bamboo Craft MSMEs as an Effort to Strengthen the Competitiveness of Gudang Village, Sumedang - Mutmainnah, Siti; Sri Harini; Tini Kartini; Endang Silaningsih; Danu Suryani (International Journal of Educational and Life Sciences, 2024)
This service was carried out in Gudang Village, Tanjungsari District, Sumedang Regency, with the aim of strengthening the competitiveness of the village. The service team applies observation methods, program idea design, program mentoring, monitoring, and evaluation. The results of this service show the success of the program in creating superior village products, achieving targets in sales realization, improving the economy, and the satisfaction of the target community with activities